Anteseden Kualitas Laporan Keuangan BUMDes - Hapsari, Tifa Anggun; Yuliani, Nur Laila; Purwantini, Anissa Hakim (Journal of Culture Accounting and Auditing, 2024)
Village-Owned Enterprises (BUMDes) play an important role in encouraging rural social and economic development, where BUMDes is one of the entities that can encourage an increase in Village Original Revenue (PAD). This study aims to empirically test and analyze the effect of human resource competence, information technology utilization, and internal control on the quality of financial reports on BUMDes in Temanggung Regency. This research is a quantitative study with data sources using primary data obtained through distributing questionnaires. The population of this study were 30 BUMDes in Temanggung Regency. The sampling technique used purposive sampling method director, secretary, treasurer, and financial staff. The number of samples in this study were 109 respondents. The data analysis method uses multiple linear regression. The results of this study indicate that human resource competence, information technology utilization, and internal control have a positive effect on the quality of financial statements.